Collateral Consequences of School Suspension: Examining the ‘Knifing off’ Hypothesis - Novak, Abigail (American journal of criminal justice, 2021)
School exclusionary practices are routinely used in response to undesired behaviors in the school environment and have been shown to have resulted in unintentional or collateral consequences for youth, including increased risk of arrest, offending behavior, and incarceration. Little research has been done on how school exclusion impacts interaction with prosocial peers and involvement in prosocial opportunities. This study applies the labeling perspective’s knifing off concept to examine whether prosocial exposures and deviant peer associations mediate the relationship between school suspension, arrest, and offending behavior. Using data from the LONGSCAN study, we examined whether suspension led to changes in prosocial peer association and activity involvement, increases in deviant peer association, and ultimately arrest and offending behavior. Results provided support for the labeling perspective’s hypotheses, finding school suspension was indirectly associated with both arrest and offending behavior via decreases in prosocial exposures and increases in deviant peer associations. Findings suggest policy makers should consider alternatives to school suspension where possible to avoid collateral consequences like reductions in prosocial exposures and deviant peer associations and should consider applying restorative approaches following a suspension experience to reintegrate youth into prosocial communities.